Isolation and Characterization Chemical Compounds From N-Hexane Extract of Zodia Leaves (Evodia suaveolens Scheff.) - Mutakin Mutakin; Wina Yunita; Titi Wirahardja Nikodemus (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Zodia (Evodia suaveolens Scheff.) (Rutaceae) is one of Indonesia's native plants, which comes from Papua which is widely used as traditional medicine. Empirically, zodia leaves are used as anti-mosquitoes, dysentery drugs, boiled bark is useful as a reliever for malaria fever, leaf decoction is used as a tonic, and increases stamina. Until now, no investigation has been carried out for the main compounds of the zodia leaf n-hexane extract which have proven activity. Therefore, it was done the isolation and characterization of the main compound in the zodia leaf n-hexane extract (Evodia suaveolens Scheff.). Zodia leaves were extracted with n-hexane using the Soxhlet tool. The n-hexane extract was fractionated using column chromatography with a gradient of n-hexane-chloroform mixture. Isolates were isolated in the form of white needle crystals which were purified by washing with n-hexane. Isolates were characterized by analyzing various UV, IM, 1D and 2D RMI spectrometry data which were confirmed by analyzing the mass spectrum. Based on the results of spectrometric analysis, it is known that the isolate is thought to be a triterpenoid compound, namely neohop-13 (18) -ene-3α-ol.Keywords: Evodia suaveolens, neohop-13(18)-ene-3α-ol, triterpenoide,